PROBLEMS OF DEVELOPING BIOLOGICAL LITERACY IN SCHOOL STUDENTS BASED ON AN INTEGRATIVE APPROACH - Abduraxmonova Sh. A. (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the problems of developing biological literacy of schoolchildren in connection with other subjects are studied.